PENGARUH IKLAN TERHADAP PEMBENTUKAN BRAND AWARENESS DAN MINAT PEMBELIAN ULANG PRODUK - Wahyuningsih, Roy (Magister Manajemen Universitas Wisnuwardhana, 2020)
The competitor that must be faced by the Mie Sedaap Company is that the Noodles should move aggressively to increase consumer awareness in order to increase customer growth. For this reason, this research focuses on the issue of how advertising can shape brand awareness and repurchase interest. To answer the problems that have been formulated, it is necessary to obtain data relating to the research variables. Data on advertising, brand awareness, and repurchase interest were collected from 30 respondents using a questionnaire. The collected data is then analyzed using Simple Linear Regression analysis techniques. Based on the results of the analysis, then In accordance with the results obtained in this study from the descriptive statistics seen from the value of F = 19,197 (p = 0,000), while advertising and interest in constant repurchase (a) obtained 0.837 results, regression coefficient (b) obtained 0.866 results , prediction of the relationship between the effect of advertising on the repurchase interest. This can be seen from the value of F = 111,807 (p = 0,000). The results of this study can be seen that respondents strongly respond positively to sadaap noodle products, and advertising is indeed very influential on the formation of brand awareness and interest in repurchasing delicious noodle products. Keywords: advertising, brand awareness, and interest in product repurchase